Effects of Birthing Room Design on Maternal and Neonate Outcomes: A Systematic Review. (July 2020) - Nilsson, Christina; Wijk, Helle; Höglund, Lina; Sjöblom, Helen; Hessman, Eva; Berg, Marie
Aim: To summarize, categorize, and describe published research on how birthing room design influences maternal and neonate physical and emotional outcomes. Background: The physical healthcare environment has significant effects on health and well-being. Research indicates that birthing environments can impact women during labor and birth. However, summaries of the effects of different environments around birth are scarce. Methods: We conducted a systematic review, searching 10 databases in 2016 and 2017 for published research from their inception dates, on how birthing room design influences maternal and neonate physical and emotional outcomes, using a protocol agreed a priori. The quality of selected studies was assessed, and data were extracted independently by pairs of authors and described in a narrative analysis. Results: In total, 3, 373 records were identified and screened by title and abstract; 2, 063 were excluded and the full text of 278 assessed for analysis. Another 241 were excluded, leaving 15 articles presenting qualitative and quantitative data from six different countries on four continents. The results of the analysis reveal four prominent physical themes in birthing rooms that positively influence on maternal and neonate physical and emotional outcomes: (1) means of distraction, comfort, and relaxation; (2) raising the birthing room temperature; (3) features of familiarity; and (4) diminishing a technocratic environment. Conclusions: The evidence on how birthing environments affect outcomes of labor and birth is incomplete. There is a crucial need for more research in this field.